Molecular Characterization of Virulence and Antibiogram profile of Pseudomonas aeruginosa Isolated from Chronic Suppurative Otitis Media Patients, Al-Nasiriyah City, Iraq. - Muslim Dhahr Musa (University of Thi-Qar Journal of Science, 2021)
This study was conducted to characterize the virulence of P.aeruginosa isolated from Chronic Suppurative Otitis Media (CSOM) in a particular area at the south of Iraq, Al-Nasiryah City. Conventional bacteriological methods were used to isolate and identify P.aeruginosa. Polymerase chain reaction  (PCR) with a specific primer that targeting outer membrane Liporpotien L gene (OprL) was used to detect P.aeruginosa. The following virulence genes were screened; ToxA, LasB and LasA. Results indicated that the majority of CSOM was attributed to bacterial infection(83.4%) in comparison with only 2(5.6%) were fungal infections. P.aeruginosa was the most predominant species (36.7%) followed by S.aurues, Proteus Spp. and E.coli. Virulence profile revealed that all strains of P.aeruginosa were harboring at least one virulence gene. ToxA gene was found in most strains (90.1%) followed by LasB gene (81.8%) and LasA gene (63.6%). According to different combination of virulence genes, P.aeruginosa can be categorized into four genotypes with high prevalence (63.6%) of the most virulent genotype (ToxA+ LasA+  Las B+) followed by genotype (ToxA+ LasA- Las B+) (18.6%) while the genotypes (ToxA+  LasA-   LasB and  ToxA+  LasA- LasB-) were found in lowest percentage (9.1%). Additionally, all strains were able to form a biofilm with varying propensity however, the strong biofilm strains were found in a high percentage (72.7%) in genotype (ToxA+ LasA+  Las B+). Antibiogram analysis revealed that high resistance rate against otototic antibiotics including; Erythromycine, Ciprofloxacin(63%), Gentamycin, Ofloxacin and Ceftriaxone were(47.4%, 47.3% and 42.1% respectively). In conclusions, the P.aeruginosa causing CSOM in Al-Nasiriyah city is highly virulent and have a great ability to form biofilm, which could protect it from most commonly used antibiotics especially those used in Al-Nasiriyah, so it is highly recommended to seek for alternative treatment.